Value of immunogenicity in the TNF-α inhibitor treatment of rheumatic diseases - N. V. Chichasova (Современная ревматология, 2016)
Immunogenicity, the characteristic property of proteins affecting an immune response, shows up in the formation of anti-drug antibodies (ADA) and/or immune complexes. The paper discusses whether immunogenicity has an impact on the efficacy and safety of TNF-α inhibitors (TNF-αI) in different rheumatic diseases. It provides evidence that immunogenicity has an impact and no impact on the pharmacodynamics and pharmacokinetics of the drugs. It also demonstrates the detection rate of ADA when using different biological agents (BAs) in rheumatoid arthritis, ankylosing spondylitis, psoriatic arthritis, psoriasis, and Crohn's disease. The impact of TNF-αI change, concurrent methotrexate (MT) therapy, and treatment intervals on immunogenicity is characterized. A combination of TNF-αI and MT versus BA monotherapy is shown to diminish immunogenicity; moreover, the use of therapeutic doses of MT as compared to its low weekly doses (2.5–5 mg) could reduce to a greater degree the rate of anti-TNF-αI antibody formation. Randomized controlled trials have demonstrated that the presence or absence of ADA affects the rate of adverse reactions (ARs) (due to infusion or injectable therapy) than the change in TNF-αI efficacy. This is confirmed by the data of real clinical practice (BA registers from different countries), which show that there is no significant difference in the duration of treatment with different TNF-αI; therapy with the latter in the presence of ADA was shorter mainly because of ARs rather than its inefficiency. ADA detecting methods and the complexity of their interpretation are depicted.